Front Cover: Quantitative Proteomic Analysis of Low Linolenic Acid Transgenic Soybean Reveals Perturbations of Fatty Acid Metabolic Pathways. Issue 7 (4th April 2019) - Islam, Nazrul; Bates, Philip D.; Maria John, K. M.; Krishnan, Hari B.; J. Zhang, Zhanyuan; Luthria, Devanand L.; Natarajan, Savithiry S.
Abstract : DOI:10.1002/pmic.201800379 In article number1800379, Nazrul Islam et al. compare protein profile changes in normal and low linolenic acid transgenic soybeans using high‐throughput tandem mass tag (TMT) based mass spectrometry. Proteomic analysis of the transgenic line unveils changes in several key enzymes involved in fatty acid metabolism. These results will be important for the understanding how plants adjust their biochemical processes when the genetic makeup changes.